2021
DOI: 10.1080/15412555.2020.1864725
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1 Antitrypsin Deficiency and Tobacco Smoking: Exploring Risk Factors and Smoking Cessation in a Registry Population

Abstract: The ZZ genotype of alpha-1 antitrypsin deficiency (AATD) is strongly associated with COPD, even in never-smokers. Moderate AATD genotypes (MZ and SZ) have been shown to increase the severity of COPD in smokers. In this comparative study, we examine the association between AATD, genotypes, and smoking cessation. Two hundred and ninety-three Irish people with AATD [MZ (n ¼ 91), SZ (n ¼ 72), and ZZ/rare (n ¼ 130)] completed a custom questionnaire assessing their social and smoking histories. The primary outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…In a recently published study by Franciosi et al . [17,18], of 293 Irish people with AATD [ZZ ( n = 230); SZ ( n = 72); and MZ ( n = 91)], the authors found that increasing genotype severity corresponded with a lower likelihood of current smoking status (2.5% vs. 17% vs. 16% for ZZ, SZ, and MZ, respectively). Another previously published prospective study that followed patients for 3 months also suggested that a diagnosis of ZZ-AATD resulted in greater abstinence and reduced tobacco consumption compared with non-AATD smokers [19].…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published study by Franciosi et al . [17,18], of 293 Irish people with AATD [ZZ ( n = 230); SZ ( n = 72); and MZ ( n = 91)], the authors found that increasing genotype severity corresponded with a lower likelihood of current smoking status (2.5% vs. 17% vs. 16% for ZZ, SZ, and MZ, respectively). Another previously published prospective study that followed patients for 3 months also suggested that a diagnosis of ZZ-AATD resulted in greater abstinence and reduced tobacco consumption compared with non-AATD smokers [19].…”
Section: Discussionmentioning
confidence: 99%
“… 45 These findings indicate that MZ carriers, despite having a less risky genetic predisposition than ZZs to develop AATD-related diseases, may need an intensification of education and medical interventions aimed at promoting healthy lifestyles after diagnosis. 45 , 46 …”
Section: Discussionmentioning
confidence: 99%
“…45 These findings indicate that MZ carriers, despite having a less risky genetic predisposition than ZZs to develop AATD-related diseases, may need an intensification of education and medical interventions aimed at promoting healthy lifestyles after diagnosis. 45,46 MZ heterozygotes express serum levels of AAT of 11-28 µM/L (or 62-151 mg/dL), which are approximately 60% of the normal range of MM [20-53 µmol/L (102-254)]. 4 This means that the vast majority of MZ heterozygotes express serum levels above the empirically established "protective threshold" of lungs against neutrophil elastase (ie, 11 μM/L or 57 mg/dL), a historical value mainly used to indicate augmentation therapy in emphysematous patients with severe AATD.…”
mentioning
confidence: 99%
“…Risk factors for developing lung morbidity in individuals with AATD were reported in 10 studies. Smoking was cited as a risk factor in six studies [26,35,[47][48][49][50], and current smoking, age (40-59 years) and frequent severe exacerbations of COPD were associated with an accelerated decline of FEV 1 in individuals with severe AATD [26,35]. The remaining studies did not examine the influence of smoking on risk.…”
Section: Clinical Burden Reviewmentioning
confidence: 99%